التفويض وعلاقته بالولاء التنظيمي للعاملين " دراسة ميدانية في الإدارة العامة لمصرف التضامن الإسلامي الدولي " - لمشرقي, مجاهد يحيى صالح (Journal of Amran University, 2022)
This study aims to investigate the relationship between delegation and organizational loyalty of workers in the General Administration of Islamic Tadamon Bank, and find out the impact of demographic variables, represented by: gender, academic qualifications, years of service, and training courses on delegation& organizational loyalty. To achieve the objectives of the study and testing of hypotheses, a special questionnaire were developed to gather data from a sample, which contained (99) employees, and the number of questionnaires were subject to analysis (85), representing (85.9%) of the total questionnaires distributed. The study found a strong positive correlation between delegation and organizational loyalty which is statistically significant at the level of significance of (0.01), and show a significant impact statistically significant to the independent variable of delegation on the dependent variable which is the organizational loyalty, as well as nonexistence the of statistically significant differences between the views of members of the research sample towards delegation and organizational loyalty attributable to the variables of: gender, academic qualification, years of service, and training courses the level of significance values which were calculated for variables, were larger than the tabular value (0.05).